Recycling Dam Tailings as Cemented Mine Backfill: Mechanical and Geotechnical Properties. (13th April 2022) - Kasap, Tugrul; Yilmaz, Erol; Guner, Nihat Utku; Sari, Muhammet
Abstract : As a result of developing technology and scientific studies, employing dam tailings as critical raw material and vital economic reserve has become widespread recently. Employing dam tailings as a main ingredient of CPB (cemented paste backfill) can offer benefits to mining operations. This study deals with the use of dam tailings in CPB, considering the mechanical and geotechnical aspects. CPB was prepared at fixed solid and cement contents (72%, and 5%, respectively) and tested for different cure ages varying from 3 to 56 days. The results disclosed that the strength of filling increased over time, with the exception of 56-day cured CPB having high sulfur minerals where strength decreased sharply. The reasons behind these strength surges could be clarified by CPB's basicity, which quickens the hydration of cement. Voids between tailings grains are also occupied by hydration products, resulting in the high strengths. Due to the fact that higher sulfate contents can cause lower pH values within CPB, this is one of the factors that should be considered for the backfill's strength performance. The cement tends to increase the backfill's pH in short term, but pH of long-term cured backfills decreases because of dam tailings which is inclined to acid formations and erosions. This is a sign that the deformation properties of CPB are deteriorated. Depending on curing time, CPB's water content and void ratio decrease, but their surface areas increase. The resulting data will endow to better apprehend the effects of dam tailings on CPB quality integrating cost and quality.